From Imperialism to Globalization: The Transfer of Sport Forms. Issue 1 (2nd January 2022) - Gems, Gerald R.; Pfister, Gertrud
Abstract: Sport historians have lamented the dearth of studies relative to Asian sport. While scholars have begun to rectify this omission, there is still much to learn relative to the international sporting interchange and ramifications for the current geopolitical world. This examination reflects upon the Western imperialistic transfer of sport forms and the reverse cultural flow that brought Asian sport forms to the West. Our research questions address this transformation over time. What role did sport play in the colonization process? How did colonial populations react to such impositions? How and why did the emergent reversal of cultural flow transpire? We conduct a historical survey of sport in the socialization process, and its political and economic benefits to colonizers. We invoke hegemony as a continual power struggle between East and West played out over the centuries and still contested as a cultural borderlands where ideas and practices are exchanged over time. We invoke primary and secondary sources to analyze racial, nationalistic, and religious motives in the process of cultural transmission. Analysis revealed the ability of colonized groups to co-opt the sports and games of the imperialists to serve their own needs. The rise of Asian economies allowed Eastern sport forms to assume a prominent place in the West, reversing the cultural flow.